Evaluating the effects of vitamin D Level on airway obstruction in two asthma endotypes in humans and in two mouse models with different intake of vitamin D during early-life - Zhou, Yan; Qiu, Yali; Bao, Wuping; Han, Lei; Xue, Yishu; Zhang, Yingying; Tian, Xue; Fu, Qiang; Lv, Chengjian; Yin, Dongning; Zhang, Min (Frontiers in Immunology, 2023)
Asthma is primarily divided into two categories: type 2 (T2-high) and non-type 2 (T2-low). A relationship between asthma severity and vitamin D deficiency has been identified, but its impact on each asthma endotype remains unknown. We clinically examined the influence of vitamin D on patients with T2-high (n = 60) or T2-low asthma (n = 36) compared with controls (n = 40). Serum 25(OH)D levels, inflammatory cytokines and spirometry were measured. Mouse models were then used to further analyze the effects of vitamin D on both asthmatic endotypes. BALB/c mice were fed with vitamin D-deficient (LVD), -sufficient (NVD), or -supplemented diets (HVD) throughout lactation and offspring followed the same diet after weaning. Offspring were sensitized/challenged with ovalbumin (OVA) to establish “T2-high” asthma or OVA combined with ozone exposure (OVA + ozone) to induce “T2-low” asthma. Spirometry and serum, bronchoalveolar lavage fluid (BALF), and lung tissues were analyzed. Serum 25(OH)D levels were decreased in asthmatic patients compared with controls. Patients with vitamin D deficiency (Lo) had varying degrees of elevation of the pro-inflammatory cytokines IL-5, IL-6, and IL-17A, decreased expression of the anti-inflammatory cytokine IL-10, and altered forced expiratory volume in the first second as a percentage of predicted value (FEV1%pred) in both asthmatic endotypes. Vitamin D status had a stronger correlation with FEV1%pred in T2-low asthma than T2-high asthma, and 25(OH)D level was only positively linked to maximal mid-expiratory flow as a percentage of predicted value (MMEF%pred) in the T2-low group. Inﬂammation, hyperresponsiveness, and airway resistance (RL) was increased in both asthma models compared with controls while vitamin D deficiency further increased airway inflammation and airway obstruction. These findings were particularly prominent in T2-low asthma. The potential function and mechanisms of vitamin D and both asthma endotypes should be studied individually, and further analysis of the potential signaling pathways involved with vitamin D on T2-low asthma is warranted.